Contexto climático y parámetros meteorológicos en la ciudad de Tosagua, Manabí - Ecuador - Saltos Intriago, Nathalia Melissa (2025)
This research evaluated the climatic context and meteorological parameters in Tosagua city, Manabí, Ecuador. The climate type in the study area was identified by applying the Whittaker diagram through the collection of historical precipitation and temperature data, between the years 1995 and 2022, for subsequent forecasting based on the HAD CM3 climate projection model in three scenarios: A1B, B1, and A2. The Pearson correlation coefficient was used to analyze the relationship between meteorological parameters: precipitation, temperature, solar radiation, UV index, and humidity. The results showed that, during the period 1985 - 2022, the climate presented an arid tropical forest biome; while climate projections for the A1B scenario, the temperature ranged from 26.06°C to 30.07°C, precipitation increased from 290.39 mm to 346.44 mm. In scenario B1, temperature ranged from 25.33 ºC to 28.82 ºC, and precipitation from 273.62 mm to 309.79 mm; in scenario A2, temperature ranged from 25.53 ºC to 30.38 ºC, and precipitation from 274.33 mm to 342.92 mm. Correlations between meteorological variables are notable, including: temperature and daytime solar radiation, a considerable positive correlation from 0.82; the daytime UV index and daytime solar radiation from 0.54, with a medium positive correlation; and temperature versus precipitation from 0.46, with a weak positive correlation. Finally, a guide to prevention, mitigation, and adaptation strategies in a climate context was proposed to provide guidance and information through technical guidelines for improving community resilience and preparedness for extreme climate events.